2007
DOI: 10.1007/s10734-007-9084-2
|View full text |Cite
|
Sign up to set email alerts
|

Religion and attitudes of college preservice teachers toward students with disabilities: implications for higher education

Abstract: The study examined attitudes toward school inclusion of students with disabilities of 1,145 prospective teacher trainees from six national/religious groups in eleven colleges in Israel: The groups were secular, religious and ultra-orthodox Jews and Muslim, Christian and Druze Arabs. Participants responded to the ''Opinion Related to Inclusion Scale''. Trainees in all six groups supported the principle of inclusion while simultaneously recognizing the need for segregated special education placements. Several si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(41 reference statements)
3
19
0
Order By: Relevance
“…A special education survey course does indeed improve candidates' knowledge and attitudes about adapting their teaching for students with disabilities. This study supports the findings of other research conducted throughout the world (Forlin, et al, 2009;Leyser & Romi, 2008;Forlin, et al, 2003;and, Shade & Stewart, 2001).…”
Section: Purposesupporting
confidence: 92%
See 1 more Smart Citation
“…A special education survey course does indeed improve candidates' knowledge and attitudes about adapting their teaching for students with disabilities. This study supports the findings of other research conducted throughout the world (Forlin, et al, 2009;Leyser & Romi, 2008;Forlin, et al, 2003;and, Shade & Stewart, 2001).…”
Section: Purposesupporting
confidence: 92%
“…The inclusion of students with disabilities is now a world-wide practice (Leyser & Romi, 2008;Brownlee & Carrington, 2000;Hegarty, 1998;and, Sebba & Ainscow, 1996). "Teachers set the tone of classrooms, and as such, the success of inclusion may well depend upon the prevailing attitudes of teachers as they interact with students with disabilities in their classrooms" (Carroll, Forlin & Jobling, 2003, p. 65).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigating attitudes toward individuals with disabilities frequently consolidate all disabilities into one homogeneous group and fail to address differences in attitudes toward specific groups with disabilities (Bean & Hedgpeth, 2014;Bogart, Logan, Hospodar & Woekel, 2019;Culp et al, 2017;Hergenrather & Rhodes, 2007;Leyser & Romi, 2008;Palmer et al, 2000;Polo Saánchez, Fernaández-Jimeánez & Fernaández-Cabezas, 2018;Seo & Chen, 2009;Suthakaran et al, 2011;Wagner & Stewart, 2001). However, research has indicated that most individuals exhibit hierarchical preferences for specific groups of individuals with disabilities.…”
Section: Treating Disabilities As a Homogeneous Groupmentioning
confidence: 99%
“…Research on attitudes toward disabilities specifically among students in college settings can be traced back to the 1960s (Freed, 1964). While research on attitudes toward disabilities among students in college settings has been documented in the literature (e.g., Culp, Rojas-Guyler, Vidourek & King, 2017;Leyser & Romi, 2008;Palmer, Redinius & Tervo, 2000;Seo & Chen, 2009;Wagner & Stewart, 2001), a majority of the extant studies display two critical methodological limitations: (a) problems in contextualizing attitude measurement and (b) treating all disability categories as a homogeneous group. These issues may potentially bias findings and the interpretations of the results.…”
mentioning
confidence: 99%
“…As, for example, Leyser and romi (2008) have shown in a study of teacher trainees from different national/religious groups within the Israeli system of higher education, there is substantial within-system variation on a wide range of institutional and/or cultural characteristics that can yield important comparative insights. A particular effort will be made to identify research that, while conducted in one national setting, is theoretically developed and configured in such a way as to lend itself well to further and internationally comparative studies.…”
Section: International Research On Higher Education: Of Scope Focusmentioning
confidence: 99%